A Feminist Methodology of Age-Grading and History in Africa. Issue 2 (13th April 2020) - Decker, Corrie
Abstract: Age is an essential category of analysis for African history. For over a century, social scientists have emphasized the central role of age-grading in African cultures. Whereas most people in precolonial African societies assessed age in relative terms (juniors vs. seniors), European colonialism expanded the legal importance of chronological age. Gender mattered to both definitions of age. Faced with two incommensurable systems for understanding life stages—one based on relational (male) seniority and the other on chronological age—African women growing up during the colonial period found new ways to assert a sense of belonging among generations of women. I argue in favor of a feminist methodology that recognizes the broader trend among a generation of young women in Africa who employed conflicts over age to assert their maturity, and in doing so located themselves in their own histories. Identifying female age sets and generations thus offers new perspectives on how African girls and women make and remake history.